2015
DOI: 10.3390/molecules201119648
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Antifungal Extracts from Ficus hirta Fruits Using Response Surface Methodology and Antifungal Activity Tests

Abstract: Abstract:The fruits of Ficus hirta (FH) display strong antifungal activity against Penicillium italicum and Penicillium digitatum. In order to optimize the extraction conditions of antifungal extracts from FH fruit, various extraction parameters, such as ethanol concentration, extraction time, solvent to solid ratio and temperature, were chosen to identify their effects on the diameters of inhibition zones (DIZs) against these two Penicillium molds. Response surface methodology (RSM) was applied to obtain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 29 publications
4
39
0
Order By: Relevance
“…fruits have strong antifungal, antioxidant, and antiseptic effects [28,29]. Our previous studies have been demonstrated that HFE was able to significantly inhibit both P. italicum and P. digitatum in vitro [21,30]. In the present work, we found that HFE had an abundance of antioxidants and more effective DPPH, OH, ABTS radical scavenging activities, and Fe 3+ reducing power than ascorbic acid in different solvent extracts (data not shown).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…fruits have strong antifungal, antioxidant, and antiseptic effects [28,29]. Our previous studies have been demonstrated that HFE was able to significantly inhibit both P. italicum and P. digitatum in vitro [21,30]. In the present work, we found that HFE had an abundance of antioxidants and more effective DPPH, OH, ABTS radical scavenging activities, and Fe 3+ reducing power than ascorbic acid in different solvent extracts (data not shown).…”
Section: Discussionsupporting
confidence: 60%
“…The fruits of hairy fig (origin: Guangdong, China) were purchased from Huafeng herbs store in Zhangshu (Jiangxi, China) and powdered in a grinder (less than 20 mesh) after drying below 40 • C. The HFE was obtained using an ultrasonic-assisted method, as described below [21]. The air-dried mixture of 100 g powder sample was suspended in 3.1 L 90% ethanol (v/v) at 51 • C with ultrasonic-assisted extraction (40 kHz) for 65 min.…”
Section: Extraction Of Hfementioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect of ultrasonic time on the extraction of phenols from olive leaves was observed by Ahmad-Qasem et al [32]. The results showed that within too short a time the antioxidants could not be completely extracted from Thelephora ganbajun , whereas the extraction time beyond 10 min was unnecessary, which could increase the energy costs and cause the degradation of the antioxidants [30,33]. Therefore, 10 min was adopted for the subsequent experiment.…”
Section: Resultsmentioning
confidence: 57%
“…Different ethanol concentrations had different polarities. Lower concentration of ethanol is suitable for extracting the polar antioxidant compounds, whereas higher concentration of ethanol favors the less polar ones [30]. The effects of ethanol concentration were determined in the range of 10%–80% ( v / v ) under the conditions of solvent to solid ratio 30:1 mL/g, ultrasound time 30 min, temperature 40 °C and power 800 W. As shown in Figure 1A, when the concentration of ethanol increased from 10% to 60%, the Trolox equivalent antioxidant capacity (TEAC) values increased significantly from 37.51 ± 3.62 to 221.29 ± 16.78 µmol Trolox/g DW (Trolox obtained from Sigma Chemical Co., St. Louis, MO, USA), while a decreased trend in the extraction efficiency of antioxidants was observed when the concentration of ethanol was higher than 60%.…”
Section: Resultsmentioning
confidence: 99%